142k views
4 votes
Solve for g. 9 +3.59 = 11 - 0.59 9 = g=

Solve for g. 9 +3.59 = 11 - 0.59 9 = g=-example-1
User JohnAllen
by
5.3k points

1 Answer

2 votes

Vita, this is the solution:

9 + 3.5g = 11 - 0.5g

Like terms:

3.5g + 0.5g = 11 - 9

4g = 2

Dividing by 4 at both sides:

4g/4 = 2/4

g = 1/2 or g = 0.5

Let's prove g = 1/2 is correct, as follows:

9 + 3.5 (1/2) = 11 - 0.5 (1/2)

9 + 1.75 = 11 - 0.25

10.75 = 10.75

Therefore, g = 1/2 or g = 0.5 is correct

User Stephen Holiday
by
4.6k points